2023
DOI: 10.1101/2023.11.09.566405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory kinase KdpD is a tandem serine histidine kinase controlling K+pump KdpFABC on the translational and post-transcriptional level

Jakob M Silberberg,
Sophie Ketter,
Paul JN Böhm
et al.

Abstract: Two-component systems (TCSs), consisting of a histidine kinase (HK) and a response regulator, serve signal transduction in bacteria, often regulating transcription in response to environmental stimuli. Here, we identify a tandem serine histidine kinase function for KdpD, previously described as a HK of the TCS KdpDE, which controls production of the K+pump KdpFABC. We show that KdpD additionally mediates an inhibitory serine phosphorylation of KdpFABC at high K+levels, using not its C-terminal HK domain but an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is possible that such a connection between intracellular sensing and phosphatase activity does not exist in C. crescentus, which would explain why KdpD mainly acts as a phosphatase. Recently, it was reported that E. coli KdpD also works as serine kinase in high K + concentrations to control KdpB ATPase activity and ultimately stop Kdp-dependent K + transport (57). The phosphorylated serine residue in KdpB as well as the two Walker (A and B) domains in tandem driving the serine kinase activity of KdpD are highly conserved in C. crescentus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that such a connection between intracellular sensing and phosphatase activity does not exist in C. crescentus, which would explain why KdpD mainly acts as a phosphatase. Recently, it was reported that E. coli KdpD also works as serine kinase in high K + concentrations to control KdpB ATPase activity and ultimately stop Kdp-dependent K + transport (57). The phosphorylated serine residue in KdpB as well as the two Walker (A and B) domains in tandem driving the serine kinase activity of KdpD are highly conserved in C. crescentus (Fig.…”
Section: Discussionmentioning
confidence: 99%